Clinical Trial of Pap-salt Solution in the treatment of dehydrated Children. - Olanrewaju DM; Olusanya O; Oluwole FA (Nigerian Journal of Paediatrics)
Summary: In a randomised clinical trial, the efficacy of Pap-salt solution (PSS) was compared with the WHO oral rehydration salt (ORS) solution in 212 children, aged between six months and five years. All the children who received PSS were successfully treated and there was no difference (p>0.05) in the post-treatment values of the serum electrolytes in the two groups of children. Pap salt solution was acceptable to the patients, readily available and much cheaper than the ORS solution. PSS is, therefore, recommended for the rehydration of children with mild and some degree of dehydration in situations where ORS solution is not available.